Engaging the Materiality of the Archive in the Digital Age. Issue 4 (December 2016) - Tebeau, Mark
This article asks how public audiences are negotiating the material world of archives and artifacts in the digital age. The digital age would seem to have diminished the physical experience of the archive and artifact, creating a world of pure information. However, the binary of virtual and physical obscures more than it explains. In recent years, digital tools have begun to reconnect public audiences to the physical world in sometimes surprising ways. This article draws examples from interpretive projects using mobile devices, crowdsourcing in museum environments, and explorations of digital audio to show how physical experiences of cities, museums, and sound have taken on greater interpretive weight and salience as a result of digital interventions. Finally, it considers the implications of such digital interventions for curatorial practice, asking how digital tools can accentuate the ways that history is both contained in and expressed through material archives and artifacts.